2017
DOI: 10.1002/app.46098
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous decision analysis on the structural and mechanical properties of polymeric microcellular nanocomposites foamed using CO2

Abstract: In this study, the effects of nano Fe 2 O 3 content and foaming temperature and time are investigated on the various structural and mechanical properties of polypropylene in a batch foaming process with CO 2 using Taguchi approach. Cell size, relative density, and specific impact strength and hardness are considered as different criteria. The results indicated that the cell sizes are below 10 lm and a 20% improvement is observed in the microcellular nanocomposite samples containing 4 wt % nano Fe 2 O 3 . A 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…It has been shown that by adding 2 wt% of Fe 2 O 3 to polypropylene, the cell density is increased by 2.5 times. 53 The effect of the weight percentage of nanoclay on the cell density of acrylonitrile butadiene styrene (ABS) foams has been investigated, and it has been observed that by adding 2 wt% of nanoclay, the cell density of ABS foams is improved approximately by 8 times. 54…”
Section: Strategies To Increase the Cell Density/decrease The Cell Sizementioning
confidence: 99%
“…It has been shown that by adding 2 wt% of Fe 2 O 3 to polypropylene, the cell density is increased by 2.5 times. 53 The effect of the weight percentage of nanoclay on the cell density of acrylonitrile butadiene styrene (ABS) foams has been investigated, and it has been observed that by adding 2 wt% of nanoclay, the cell density of ABS foams is improved approximately by 8 times. 54…”
Section: Strategies To Increase the Cell Density/decrease The Cell Sizementioning
confidence: 99%
“…As shown in Figure 1a, the compression deformation process of the samples proceeds in three stages. Accordingly, the curve can be divided into three stages: a linearly elastic phase, uniform phase and compaction phase (19)(20)(21)(22). Under the same strain, the corresponding stress decreases with the increase in foaming temperature.…”
Section: Compressive Performance Analysis 311 Effects Of Foaming Tementioning
confidence: 99%
“…For instance, in the cable industry decreasing the density through the foaming process leads to reduction of used polymer that will decrease the production expenses. [3][4][5][6][7][8] The processing of these materials is of high importance and working out a relation between structural properties and insulation behavior needs to be studied thoroughly. showed that there was a specific cell size that showed a very low break down strength.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, foaming the insulating material can affect other properties such as density and mechanical behavior. For instance, in the cable industry decreasing the density through the foaming process leads to reduction of used polymer that will decrease the production expenses 3‐8 . The processing of these materials is of high importance and working out a relation between structural properties and insulation behavior needs to be studied thoroughly.…”
Section: Introductionmentioning
confidence: 99%